Active and Passive Mixing for Immiscible Liquid-Liquid Systems: A Performance Evaluation of Novel Micro-Reactors - Mongeon, Sébastien (Université d'Ottawa / University of Ottawa, 2018)
Continuous flow reaction using micro-reactors is a valued technology due to its excellent mass and heat transfer performance, reduced reactor volume, handling capacity of hazardous reactions, and many other process intensifications. These intensifications opportunities interest the fine chemicals, pharmaceuticals producers and other multiphase reaction users who currently use batch processes or already use continuous flow. In this thesis, elements of passive and active mixing are investigated for the application of immiscible liquid-liquid systems. In the first study, the effects of geometrical arrangements of a residence time between mixing units on the interphase mass transfer rates are evaluated with four different immiscible liquid-liquid systems. A presentation of an algorithm for the optimal selection of a reactor and its operating conditions is given in order to enable easy and improved use of one’s micro-reactor. In the second study, the impact of a secondary pulse flow on interphase mass transfer is investigated. A coil without internal baffles is used as the oscillatory-flow coil reactor with a continuous active mixing source. The best application for the reactor is determined using a comparison to other complementary continuous flow platforms in the toolbox approach. The novel advancements presented here will help lead new molecular discoveries and connect the laboratory science scale to the process engineering production scale.
Keywords: micro-reactor; active mixing; passive mixing; liquid-liquid; mass transfer rate; oscillatory flow; continuous flow reactor